Determination of optimum heap height from column leach tests: 2. Sensitivity analysis. (3rd July 2017) - Apelt, T.; Forrester, K.; Short, M.; Stefan, L.
Abstract : A method to determine optimum heap leach height has resulted from design work for a uranium heap leach project on the Macusani Plateau in south-eastern Peru. An analysis of the optimum heap height estimate details its sensitivity to the constituent variables algebraically, graphically, and, in contour plot format. A comparison is drawn against a Namibian uranium project with design details in the public domain and agreement is found to be reasonable. The leach extraction model and dynamics are analysed in terms of solution to ore ratio (SOR), reaction extent and acid consumption efficiency to address model time dependence loss in the model simplification step. The rate of change in the acid efficiency is used to specify the target extraction and determine leach SOR and leach time. The validity of the optimum height estimate equation is supported by favourable comparison against the spreadsheet calculation results and data from another uranium heap leach project. The estimate is dependent on recovery discount and pad maintenance costs but is independent of theoretical recovery and pad capital costs.